Quality of Life among Yemeni Women Utilizing Intrauterine Devices and Oral Contraceptives in Selected Primary Healthcare Centers in Sana'a City, Yemen - Duaa Mutahar; Afaf Mahdi; Hajar Ahmed; Tarteel Raweh; Fatima Al-Refaei; Maleka Kasem; Wafaa Al-Awar (University of Science and Technology, Sana’a, Yemen, 2025)
Background: Various contraceptive methods are available, with intrauterine devices (IUDs) and oral contraceptive pills (OCPs) being the most widely used for fertility reduction. However, underlying health conditions may compromise the safety and effectiveness of these methods. Family planning programs primarily target women, but their impact on women's quality of life (QoL) has received limited attention. This study aimed to evaluate the influence of IUDs and OCPs on the QoL of Yemeni women attending primary healthcare (PHC) centers in Sana’a City and to examine the associations between these factors. Methods: A cross-sectional study was conducted in 2024 among 354 married women aged 14–49 years attending selected PHC centers in Sana’a City. A multi-stage cluster sampling technique was applied, where three districts were randomly selected, followed by the selection of nine PHC centers. Then, eligible women were proportionally allocated to centers and selected via systematic random sampling. Sociodemographic and contraceptive-related data were collected using a structured questionnaire, and the Arabic version of the WHO QoL Instrument (WHOQOL-BREF) was used to evaluate the influence of contraceptive use on women’s QoL across physical, psychological, social, and environmental domains. QoL scores were computed for physical, psychological, social, and environmental domains, categorized as high (> median) or low (≤ median). Associations between QoL and women’s characteristics were examined using the chi-square test, with statistical significance set at a P-value of <0.05. Results: Among the participants, 56.8% used oral contraceptive pills (OCPs), predominantly combined estrogen–progesterone formulations (45.8%), while 11% used progesterone-only pills; the remaining 43.2% used IUDs. Age was significantly associated with method choice (P <0.001), as OCPs were more frequently used by women <30 years (47.5% for combined and 59% for progesterone-only OCPs), whereas IUDs were predominant among those ≥30 years (71.2%). A significant association was also found between women’s level of education and the type of contraceptive used (P = 0.007), where illiteracy was more common among IUD users (17.6%), compared to the high literacy rates among the users of combined OCPs (89.5%) and progesterone-only OCPs (100%). Regarding QoL, the median overall score was 2.68 (range: 1.07–3.71), with nearly equal proportions of women reporting low (50.3%) and high (49.7%) QoL. Domain-specific analysis revealed the lowest perceived QoL in the environmental domain (median 3.00; 62.7% low), while the physical domain had the highest median (3.75), though more than half (55.4%) still reported low QoL. Similarly, more than half of women showed low QoL in the psychological (54.8%) and social (54.5%) domains. Illiteracy (OR = 3.9, 95% CI: 1.87–8.21; P <0.001) and rural residence (OR = 2.1, 95% CI: 1.02–4.45; P = 0.038) were significantly associated with low QoL. Conclusion: Both OCPs and IUDs are linked to low QoL among Yemeni women, particularly in the environmental domain, with no significant difference between methods. Illiteracy and rural residence show a significant influence on the well-being of women using contraceptives, underscoring the need for family planning programs to be integrated with policies that address poverty, education, and healthcare access to improve women’s overall QoL.